Multipurpose palm fruit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Although inedible, the fruit of desert palms, Balanites aegyptiaca, can be a source of pharmaceutical products, pesticides, edible oil, soap and even fuel. This is the conclusion of a pilot project in the Sudan financed by the United Nations...